Approach to some philosophical roots that influenced the Theory of Gender - Boluarte Drago, Analyda (2023)
Being the Gender (gender), a term that can become polysemic and perhaps more used than the term sex, it is considered crucial to go to the root of the philosophies that have been the basis for the construction of the Gender Theory as it is described, as it is currently proposed. Without claiming to be exhaustive, we present some modern and contemporary philosophers who may have had a relevant impact in this subject. In the first section, we will mention the so-called ”masters of suspicion” highlighting the influence and impact left by their postulates. The second Section will deal with three philosophers who, having inherited the proposals of their predecessors, each one emphasizes poststructuralist approaches.